2022
DOI: 10.3390/polym14194131
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Oxaliplatin-Loaded Iodine Nanoparticles for Chemoradiotherapy of Human Colorectal Cancer (HT-29) Cells

Abstract: Colorectal cancer is highly prevalent worldwide and has significant morbidity and mortality in humans. High-atomic-number nanoparticles such as iodine can act as X-rays absorbers to increase the local dose. The synthesis and fabrication of oxaliplatin-loaded iodine nanoparticles, their characterization, cell toxicity, radiosensitivity, cell apoptosis, and cell cycle assay in human colorectal cancer (HT-29) cells are investigated. Results show that the synthesis of a new iodine nanoparticle, polymerized triiodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…In addition, methods like IGRT, IMRT, and tomotherapy have been investigated by many researchers. In most studies, gold nanoparticles (AuNPs) were used as a radiosensitiser, but the use of AuNPs has many limitations that make it unable to use extensively in clinical applications [6]. In the current study, the new update of bismuth‐based NPs was investigated in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, methods like IGRT, IMRT, and tomotherapy have been investigated by many researchers. In most studies, gold nanoparticles (AuNPs) were used as a radiosensitiser, but the use of AuNPs has many limitations that make it unable to use extensively in clinical applications [6]. In the current study, the new update of bismuth‐based NPs was investigated in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to treatment failure and can also cause side effects in normal tissues [4]. Hence, the use of radiosensitizers may be beneficial to enhance the delivery of radiation doses to tumour cells [5].Recently, as a new radiosensitising technique in medicine, nanoparticles (NPs) may have improved the treatment of various types of tumours [6]. Therefore, many studies are limited to in vitro and in vivo conditions of nanoparticle application in radiotherapy [7,8].…”
mentioning
confidence: 99%
“…Moreover, in another study that set out to determine the effect of glucose-modified dendrimer-entrapped gold nanoparticles (Au DENPs) labeled with radionuclide 68 Ga for positron emission tomography (PET)/ CT dual-mode imaging, Li et al [27] found that 68 Ga labeled with 2-amino-2-deoxy-D-glucose (DG) DG-Au DENPs can be used for PET/CT imaging and immunotherapy of different tumor types. In this line [2], the researcher investigated the multi-modality imaging and photothermal effect of gold-doped upconverting nanoparticles (UCNPs). Zhang et al [28] pointed out that due to photothermal stability, low cytotoxicity, and high biocompatibility, Au-UCNPs-DSPE-PEG 2k may be utilized as MRI and CT contrast agents for both in vivo and in vitro, and may also be used for photothermal treatment.…”
Section: Gold-based Nanoparticlesmentioning
confidence: 99%
“…Nanoparticles in medicine have applications in developing novel therapeutic and diagnostic modalities for cancer treatment and detection [1]. In recent years, there has been growing interest in using nanoparticles in medicine, especially in medical imaging as a contrast agent, in radiation therapy as carriers for drug and gene delivery, and as a radio-sensitizer [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, publications involving AuNPs in cancer RT grew rapidly because of the high X-ray absorption coefficient and ease of synthetic manipulation, which enabled the particle’s physicochemical properties to be controlled with better precision [ 41 , 42 ]. In the coming years, other sophisticated NPs composed of heavy elements, such as titanium (Ti, Z = 22) [ 42 , 43 ], iodine (I, Z = 53) [ 44 , 45 ], gadolinium (Gd, Z = 64) [ 46 , 47 , 48 ], hafnium (Hf, Z = 72) [ 49 , 50 , 51 ], and bismuth (Bi, Z = 83) [ 52 , 53 ], have been studied extensively. Based on these studies, kV X-rays as a radiation modality can use the high photoelectric absorption cross-section and the consecutive release of secondary electrons (including Auger electrons and photoelectrons) from NREs as an advantage to further enhance the radiation effects( Figure 3 A).…”
Section: Mechanisms Of Radiosensitization By Nanomaterialsmentioning
confidence: 99%